Pemanfaatan Panas Buang Pendingin Udara untuk Proses Penguapan Air pada Sistem Desalinasi Berbasis Vortex Generator - Genta Prastanadira; Dan Mugisidi (Prosiding Seminar Nasional Teknoka, 2025)
The clean water crisis caused by climate change and population growth has driven the development of efficient and sustainable desalination technologies. One alternative is to utilize waste heat from air conditioning systems as a thermal energy source for water evaporation processes. Hot air from air conditioning system condensers can be reused in the desalination process, especially when combined with vortex generators to increase heat transfer through turbulent flow. This study aims to review various studies on the effect of vortex generators on increasing the evaporation process in air conditioning waste heat-based desalination systems. The method used is a literature study of scientific publications discussing flow characteristics, temperature distribution, thermal efficiency, and water evaporation rate. The results of the review show that the application of vortex generators can increase the evaporation rate compared to conventional systems. This study provides the basis for the development of energy-efficient desalination systems with broad potential for clean water supply.